Adsorption of phosphate from aqueous solution by vegetable biochar/layered double oxides: Fast removal and mechanistic studies. (July 2019) - Zhang, Zhaoran; Yan, Liangguo; Yu, Haiqin; Yan, Tao; Li, Xuguang
Graphical abstract: Highlights: Vegetable biochar/LDOs were synthesized for phosphate removal. Phosphate was removed efficiently, and quickly, in a solution with pH of 2–10. The reaction mechanisms were "memory effect, " electrostatic attraction, surface complexation, and anion exchange. Abstract: Two biochars, from Chinese cabbage (Cc, Brassica rapa pekinensis ) and rape (Ra, Brassia campestris L. ), were used to prepare biochar/Mg-Al layered double oxides (LDOs) as adsorbents for phosphate removal from aqueous solution. The biochar/LDOs were horizontally alternated lamellar particles and had abundant groups of oxides and biochars. The phosphate removal percentage remained above 92% at a pH range of 2–10, and above 95% during the first 5 min for 50 mg/L phosphate by 0.05 g biochar/LDOs. The adsorption kinetics and isotherms data were well fitted by the pseudo-second-order kinetic equation, as well as by the Freundlich and Langmuir models. Based on FTIR, XPS, and zeta potential analysis, the interaction mechanisms were defined as "memory effect", electrostatic attraction, surface complexation, and anion exchange. The results indicate that vegetable biochar/LDOs can be considered a novel and efficient sorbent for phosphate removal from water or wastewater.